Analisis Kegunaan Dan Penggunaan Palet Plastik. - Samsul Arifin; Maulana Rizal Mantovani; Jhourdy Novrian; Rida Ayu Yuliana; Audrey Nathania Early (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Plastic is one kind of pallet material with some advantages compared with wooden or other materials and has been well-developed in developing countries. However, for some reason, the plastic pallet has just started growing in Indonesia. Palletisation will be more efficient when applied internally or externally in the industries, compatible with vehicles and storage systems and strong enough for all cargo. Therefore, plastic pallets are made from pure materials, not recycled materials; size should conform with the requirements, be light, stable in structural design and smooth. .